Service recovery system antecedents: a contingency theory investigation. (21st May 2019) - S. Smith, Jeffery; Jayaram, Jayanth; Ponsignon, Frederic; S. Wolter, Jeremy
Abstract : Purpose: The purpose of this paper is to examine the influence of different antecedent factors (contingencies) on the design of a service recovery system (SRS). Design/methodology/approach: A conceptual model was framed and a series of hypotheses generated and tested using data from 158 practicing managers using a multivariate general linear modeling technique. Findings: The analyses indicated that firms, by and large, mainly considered environmental factors in the SRS design. Additional evidence suggests that managers do consider other contingencies but may do so in a fragmented manner. The results presented herein indicate that firms design back-office aspects of SRS in response to external factors (i.e. the environmental contingency). In contrast, the front-office components appear to have more diverse antecedents but are strongly influenced by the firm's recovery orientation. The specific recovery practices appear to be implemented per industry standards. In sum, evidence indicates that there are diverse driving factors to total SRS design. Research limitations/implications: Limitations are based primarily on the methodology as data were obtained from a single person who represented the entire SRS. Care was taken in the study design in order not to compromise the validity of the findings. Practical implications: The results indicated that managers responsible for system design need to be holistic in SRS design to more tightly link decisions across multiple contingencies so as to more fully integrate total service system design. This is potentially accomplished through the inclusion of aspects of all relevant contingencies when designing recovery systems. Originality/value: This paper's main contribution is that it employs established theory to develop and test a model to show that firms consider multiple contingencies while designing SRS. It contributes to the emerging body of work on SRS design by providing insights that can be considered as driving forces behind the design of SRS.